Zinc dampens antitumor immunity by promoting Foxp3+ regulatory T cells - Narayan, Sugandha; Dalal, Rajdeep; Rizvi, Zaigham Abbas; Awasthi, Amit (Frontiers in Immunology, 2024)
The role of zinc (Zn) in tumor development and immune modulation has always been paradoxical. This study redefines our understanding of the impact of Zn on cancer progression and therapeutic strategies. Our findings show that high dietary Zn promotes tumor progression by fostering a pro-tumorigenic environment mediated by T cells. In contrast, deficiency in dietary Zn and chelation of tissue Zn emerge as potent drivers of antitumor immunity. We elucidated that increased Zn intake facilitates tumor progression by fostering Foxp3+ regulatory T cells (Tregs) frequency. Remarkably, we have pinpointed FOXO1 as the master regulator governing the influence of Zn on Tregs, elucidating a novel mechanistic insight. Finally, we introduce a promising therapeutic approach by showing that administering Clioquinol (CQ) significantly enhances αPD-1 immunotherapy response, particularly in melanoma. These revelations transform our comprehension of the multifaceted role of Zn in tumorigenesis and immune regulation, highlighting innovative possibilities for cancer therapy.